Reduction of Nitrite in Meat Products through the Application of Various Plant-Based Ingredients - Karolina Ferysiuk; Karolina M. Wójciak (MDPI AG, 2020)
Nitrite is the most commonly applied curing agent in the meat industry, and is known to affect human health. Nitrites impart a better flavor, taste and aroma; preserve the red-pinkish color of the meat; and prevent the risk of bacterial contamination of the cured meat, especially from Clostridium botulinum. Unfortunately, recent research has demonstrated some negative effects of this technique. Certain N-nitroso compounds have been shown to stimulate gastric cancer; therefore, most of the research groups are studying the effects of nitrates and nitrites. In this review, we discuss the various food sources of nitrites and nitrates and their current legal requirements for use in meat products. We also discuss the possible changes that might come up in the regulations, the concerns associated with nitrates and nitrites in meat products, and the use of plant-based nitrite and nitrate substitutes. All these topics will be considered with respect to ensuring a high level of microbiological protection, oxidative stability and acceptable sensory quality (color, taste and smell) in meat products.